2005
DOI: 10.1212/01.wnl.0000158326.31368.04
|View full text |Cite
|
Sign up to set email alerts
|

Headache, cerebrovascular symptoms, and stroke

Abstract: Migraines and other headaches, particularly those accompanied by aura, were associated with an increased occurrence of stroke/TIA symptoms and ischemic stroke events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
170
3
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(181 citation statements)
references
References 29 publications
5
170
3
3
Order By: Relevance
“…The incidence of cerebro-and cardio-vascular events in the WHS are shown in Figure 2. Similar findings were achieved in the Atherosclerosis Risk in Communities Study (ARCS) [30], a randomized trial with a study population of 12,750 subjects of both sexes: patients with MA were found to have a 2.81 RR of ischemic stroke (95% CI: 1.6-4.92) and a 4.28 RR of transient ischemic attack (TIA) (95% CI: 3.02-6.08).The absolute increase of cerebrovascular risk is also limited for women in this age group, but is considerably greater than that of younger women: in the WHS study, 3.8 strokes per 10,000 persons-years could be attributed to MA [29].…”
Section: Association Between Migraine and Cerebrovascular Diseasessupporting
confidence: 73%
“…The incidence of cerebro-and cardio-vascular events in the WHS are shown in Figure 2. Similar findings were achieved in the Atherosclerosis Risk in Communities Study (ARCS) [30], a randomized trial with a study population of 12,750 subjects of both sexes: patients with MA were found to have a 2.81 RR of ischemic stroke (95% CI: 1.6-4.92) and a 4.28 RR of transient ischemic attack (TIA) (95% CI: 3.02-6.08).The absolute increase of cerebrovascular risk is also limited for women in this age group, but is considerably greater than that of younger women: in the WHS study, 3.8 strokes per 10,000 persons-years could be attributed to MA [29].…”
Section: Association Between Migraine and Cerebrovascular Diseasessupporting
confidence: 73%
“…Several lines of evidence suggest MA is more strongly associated with stroke than MO [3,4,12]. For our study, analysis of associations between family history of vascular risk factors and MA compared to MO found only modest positive associations, with confidence intervals that included no associations at all.…”
Section: Discussioncontrasting
confidence: 42%
“…Data from several studies suggest that migraine may be a risk factor for the development of stroke [3,4,[9][10][11][12] and MA may be an important risk factor for stroke in women [12,13]. The mechanisms that underlie these observations are unclear but a reasonable hypothesis could include the presence of shared risk factors as a possible cause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second prospective study used data from the Atherosclerosis Risk in Communities Study and included over 12,000 men and women aged 55 and older 30 . Compared to participants without headaches, migraineurs (of both subtypes) had a 1.8-fold increased risk of ischemic stroke (relative risk 1.84; 95% CI, 0.89-3.82).…”
Section: Migraine and Strokementioning
confidence: 99%